Analysis of The Implementation of Accounting Information Systems to Improving the Preparation of Financial Statements in The Sales Cycle of Oil and Gas Companies - Ayi Astuti; Indri Utami; Mentari Puteri Pertiwi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to determine the role of accounting information systems in improving the quality of financial reporting and analyzing financial reports in the sales cycle in accordance with accounting information systems theory. The data analysis technique used is descriptive analysis technique, namely how to analyze, interpret, and process oil and gas financial report data. Respondents in this study were one of the oil and gas companies in Bandung, namely PT. Puteramas Teguh Jaya by conducting a survey of 35 respondents. The type of data used in this research is qualitative data. Sources of data in this study are secondary data in the form of financial reports on oil and gas sales. Data collection techniques used in this study are interview techniques and documentation techniques regarding accounting information systems for sales financial reports. From the known research results, it is obtained as follows: Responses about the variables of this study are included in the high category, financial reports and sales cycle The results of the analysis found that there is a significant relationship between accounting information systems and financial reports, including knowledge of entrepreneurial competence with stakeholder support. interests with a fairly close relationship. The results of the analysis also found that the accounting information system and it were found simultaneously to have a significant effect on the sales cycle.